Charge generation in organic solar cells: Journey toward 20% power conversion efficiency: Special Issue: Emerging Investigators. Issue 6 (26th October 2022) - Tamai, Yasunari
Abstract: The power conversion efficiencies of organic solar cells (OSCs) have routinely lagged far behind those of their inorganic counterparts. However, owing to the enormous contributions of many researchers, the power conversion efficiencies of OSCs have rapidly improved and now exceed 19%. The charge generation mechanisms in OSCs have been heavily debated during this period while acquiring valuable knowledge. This review highlights fundamental and cutting‐edge research that rationalizes why OSCs can generate photocurrent so efficiently. In particular, a photophysicist's views on exciton diffusion to donor:acceptor interfaces, charge transfer at the donor:acceptor interface, and long‐range spatial dissociation of charge transfer states are discussed. Although a general consensus in this area has not been reached yet, recent time‐resolved spectroscopic measurements provide important photophysical insights that can help achieving a better understanding of the charge generation mechanism in OSCs. Based on these observations, future research directions for realizing further improvements in OSC performance are discussed. Abstract : Herein, a photophysicist's views on charge generation in organic solar cells is discussed. Recent steady‐state and time‐resolved spectroscopic studies regarding the exciton diffusion to donor:acceptor interfaces, charge transfer at the donor:acceptor interface, and long‐range spatial dissociation of charge transfer states are highlighted. Based on these findings, future research directions are discussed.